'Do You Hear Voices, or Do You Think You Hear Voices?': Malevolence and Modernity in the Psychiatric Clinic. Issue 1 (2nd January 2022) - Willford, Andrew
Abstract: Based upon fieldwork at India's National Institute of Mental Health and Neurosciences (NIMHANS), I trace the contours of hysteria as an enduring, albeit informal, analytic that continues to disturb neuropsychiatric reductionism within psychiatry. I argue that at this historical moment, the political and economic demand for singular identities out of more porous cultural life-worlds (e.g. ethnic, religious, linguistic, occupational) produces clinical subjects incapable of nuance and flexibility, hastening a host of possessive, literalist, legalist and 'hysteric' symptoms that overtake India's most vulnerable modern subjects, fuelling the sense of a crisis in search of a pharmaceutical solution to a psychopathological diagnosis.